Impedimetric immunosensor for atrazine detection based on polypyrrole nanowires - Anh, Nguyen Van; Quan, Nguyen Van; Binh, Nguyen Hai; Huy, Nguyen Le; Huyen, Le Trong; Lam, Tran Dai (Vietnam Journal of Science and Technology, 2015)
Animpedimetric immunosensor based on polypyrrole (PPy) nanowires was developedand applied for atrazine (ATZ) herbicide detection. In this work, the PPynanowires were synthesized by an electrochemical free-template method onto aninterdigitated platinum micro-electrode (IDµE). The immunosensors were preparedby immobilization of monoclonal anti-atrazine antibody (a-ATZ) onto a PPy surface using glutaraldehyde asa cross-linker. The electrodes were characterized using scanning electronmicroscopy (SEM), cyclic voltammetry (CV) and electrochemical impedancespectroscopy (EIS) techniques. The ATZ analysis is based on the immunoreactionof free ATZ and a-ATZ attached on top of the IDµE area (fingersand inter-digits space) by means of EIS. Thanks to immunoreagent specificity,these sensors exhibit high selectivity and sensitivity for ATZ detection with athreshold of 10 ng/mL